EFEKTIVITAS EKSTRAK DAUN SIRSAK (Annona muricate Linn) TERHADAP PERUBAHAN KADAR FRAKSI LIPID PADA TIKUS PUTIH JANTAN (Rattus norvegicus) YANG MENGALAMI DISLIPIDEMIA - Hidayati, Prema Hapsari; Gina Isni Djanuaresty Iskandar; Mufia Muin; Nurul Faiqah; Agung Sukriadi; Rahmawati Mamille (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
Introduction: Dyslipidemia is associated with mortality from cardiovascular disease. Soursop leaves are a traditional medicine that can lower blood cholesterol levels. Studies on the effectiveness of soursop leaves on cholesterol levels are lacking. Objectives: To determine the effect of soursop leaf extract (Annona muricata Linn) on changes in lipid fraction levels in white male rats with dyslipidemia. Methods: This study used one group pre-test post-test on 15 male white rats which were divided into 3 groups. The first group was given soursop leaf extract, the second group was given simvastatin and the third group was given a placebo. Results: At the start of the study, the mean total cholesterol levels in the group of rats that received Annona muricata extract were 188.4 mg/dL, triglycerides 107.4 mg/dl, LDL 94 mg/dl, and HDL 24.8 mg/dl. After treatment, the mean total cholesterol level was 136.2 mg/dL (p=0.023), triglycerides 90.4 mg/dL (p=0.018), LDL 81 mg/dL (p=0.000), HDL 28.8 mg/dL (p=0.02). Conclusion: Annona muricata L leaf extract can significantly reduce total cholesterol, LDL cholesterol, and triglyceride levels, and can also increase HDL cholesterol levels in the diet-induced hypercholesteromial rat group.